Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/chd.12647
|View full text |Cite
|
Sign up to set email alerts
|

Narrative analysis of adults with complex congenital heart disease: Childhood experiences and their lifelong reverberations

Abstract: Adults with CHD provide the voices of expert witnesses; illuminating how the pediatric journey influences their identity, choices, personal relationships and adult health care interactions. These narratives could inform and improve the contemporary care of children with heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In addition, many patients with ACHD have medical post-traumatic stress disorder or anxiety and can relate traumatic childhood medical experiences with little prompting. 23,24 This combination of an external locus of control, a preference away from receiving medical information regarding their own health, and trauma highlights the importance of multidisciplinary care for patients with ACHD. Cardiologists receive little training on how to navigate the mental health needs of their patients, and our research highlights the importance of involving psychologists and social workers in long-term ACHD care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many patients with ACHD have medical post-traumatic stress disorder or anxiety and can relate traumatic childhood medical experiences with little prompting. 23,24 This combination of an external locus of control, a preference away from receiving medical information regarding their own health, and trauma highlights the importance of multidisciplinary care for patients with ACHD. Cardiologists receive little training on how to navigate the mental health needs of their patients, and our research highlights the importance of involving psychologists and social workers in long-term ACHD care.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with ACHD-HF often recall a childhood awareness of a potentially life-threatening diagnosis, they typically do not remember having had specific conversations about that with their parents or care providers. 37 Some feel vulnerable during adult health care interactions, because they lack the information needed to understand their acute situation and make medical management choices. 37 Beyond the potential psychosocial benefits of helping young people to understand their diagnoses and potential health trajectories, there may be practical advantages of discussing ACHD-HF with at-risk patients from late childhood onwards.…”
Section: Advanced Care Planning and End-of-life Carementioning
confidence: 99%
“…37 Some feel vulnerable during adult health care interactions, because they lack the information needed to understand their acute situation and make medical management choices. 37 Beyond the potential psychosocial benefits of helping young people to understand their diagnoses and potential health trajectories, there may be practical advantages of discussing ACHD-HF with at-risk patients from late childhood onwards. For instance, it is important to understand that becoming obese, smoking, or taking drugs will not only aggravate cardiac vulnerability but may also limit the options for eventual transplant.…”
Section: Advanced Care Planning and End-of-life Carementioning
confidence: 99%
“…[ [14][15][16][17][18] Most importantly, randomised controlled trials are necessary to increase the level of evidence in the eld of CHD patient education. [19,20] In a pilot study evaluating the implementation of our own transition program, we showed that patients with complex CHD, poor disease knowledge, risk behaviours, and lower age, were more likely to join this transition program.…”
Section: Introductionmentioning
confidence: 99%